“We Just Try to Work With the Needs in Front of Us”: How Teachers in Secondary Schools Enact Ontario’s International Education Strategy - Bell, Nancy; Desai Trilokekar, Roopa (Comparative and International Education / Éducation comparée et internationale)

(untitled) (University of Western Ontario, 2022)
The Ontario government’s International Education Strategy (2015) establishes goals for international education and the hosting of international students in Ontario schools. Using a critical policy lens, we focus on teachers as key to enacting these policy objectives in local contexts. The article presents findings from four focus groups of Ontario teachers working in schools with large international student cohorts. We found teacher participants were generally unaware of a broader vision or strategic goal for the presence of these students in their schools. They found it difficult to meet the needs of this growing cohort, and they faced this challenge with varying degrees of enthusiasm. Factors that influenced their enactment included personal background and education, as well their ability to collaborate and work in contexts with a professional ethos. Overall, teachers expressed a desire for more information, support, and professional development, including opportunities for collaboration, with regard to educating international students in their schools.